Pengaruh Jumlah Nasabah Kredit dan Kredit yang Disalurkan Pada Profitabilitas Dengan NPL Sebagai Pemoderasi - Dewi, Sinta Ratna; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 22 No 2 (2018), 2018)
This study aims to obtain empirical evidence number of credit customers on profitability, effect of lending on profitability, effect the number of credit customers on profitability with Non Performing Loan as a moderator and the influence of lending on profitability with Non Performing Loan as moderator at LPD in Tabanan Regency. Sampling technique using probability sampling method, especially proportionate stratified random sampling obtained 471 samples with three years observation from 2014-2016. Data analysis technique using Moderated Regression Analysis. The results showed that the number of credit customers have no effect on profitability. Lending have a positive effect on profitability. Non Performing Loans do not moderate the effect of the number of credit customers on profitability. Non Performing Loan weakens the effect of lending on profitability. Keywords : Loan to deposit ratio, customer, non performing loan, profitability